2021
DOI: 10.1155/2021/9053280
|View full text |Cite
|
Sign up to set email alerts
|

Killer-Cell Immunoglobulin-Like Receptors (KIR) in HIV-Exposed Infants in Cameroon

Abstract: The biological reason(s) behind persistent mother-to-child transmission (MTCT) of HIV (albeit at reduced rate compared to the preantiretroviral therapy era) in spite of the successful implementation of advanced control measures in many African countries remains a priority concern to many HIV/AIDS control programs. This may be partly due to differences in host immunogenetic factors in highly polymorphic regions of the human genome such as those encoding the killer-cell immunoglobulin-like receptor (KIR) molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Among 28 studies included, we found 11 cohort studies [ 13 , 24 33 ] and 17 cross sectional studies [ 9 11 , 14 , 34 – 46 ]. Study participants were recruited between 1994 and 2017.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among 28 studies included, we found 11 cohort studies [ 13 , 24 33 ] and 17 cross sectional studies [ 9 11 , 14 , 34 – 46 ]. Study participants were recruited between 1994 and 2017.…”
Section: Resultsmentioning
confidence: 99%
“…Out of the 29 included studies, 27 studies reported data on MTCT and were considered in the final meta-analysis [ 9 11 , 13 , 14 , 24 46 ]. The pooled prevalence (95% confidence interval) rate of MTCT was 7.00% (6.07–8.51), I 2 = 93%, p<0.01 ( Fig 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Individuals encoding for the expressed KIR2-DL5A gene might therefore have an advantage in controlling HIV-1 replication. A recent study revealed an association between KIR2DL5 and reduced mother-to-child transmission of HIV-1 in infants born by HIV-1-infected mothers [46], supporting a protective role for KIR2DL5. Given the limited expression of KIR2DL5 on the cell surface, future studies need to discriminate between KIR2DL5A and KIR2DL5B genotypes when studying implications of KIR2DL5 expression on transmission and disease outcomes, and investigate this in the context of TIGIT, as it has been reported that TIGIT expression is upregulated on NK cells during HIV-1-infection [47,48].…”
Section: Plos Pathogensmentioning
confidence: 93%
“…However, there are findings that HIV can infect trophoblast cells in vitro, and HIV‐infected cells can also cross the placenta 261 . As for the KIR/HLA axis involvement in response to placental HIV infection, some authors state preferentially activating KIR receptors repertoire (KIR3DS1, KIR2DS2, KIR2DS3, KIR2DS4, and KIR2DL2) is associated with higher susceptibility to HIV‐1 infection in children while more inhibitory KIR repertoire (KIR3DL1, KIR2DL2, KIR2DL3, KIR2DL5, and KIR2DS5) interacting with HLA‐C ligands is associated with newborn protection against HIV‐1 infection 262–264 . According Paximadis et al, 265 KIR2DL2/KIR2DL3 has low expression in intrapartum‐transmitting mothers independent of the maternal viral load.…”
Section: Kir/hla Allorecognition In the Context Of Pregnancy Disorder...mentioning
confidence: 99%
“…261 As for the KIR/HLA axis involvement in response to placental HIV infection, some authors state preferentially activating KIR receptors repertoire (KIR3DS1, KIR2DS2, KIR2DS3, KIR2DS4, and KIR2DL2) is associated with higher susceptibility to HIV-1 infection in children while more inhibitory KIR repertoire (KIR3DL1, KIR2DL2, KIR2DL3, KIR2DL5, and KIR2DS5) interacting with HLA-C ligands is associated with newborn protection against HIV-1 infection. [262][263][264] According Paximadis et al, 265 KIR2DL2/KIR2DL3 has low expression in intrapartum-transmitting mothers independent of the maternal viral load. In addition, the KIR2DL3 homozygosity alone or in combination with HLA-C1C2 genotype was elevated showing weak dNK cell inhibition influence on vertical HIV-1 transmission.…”
Section: K Ir /Hl a Allorecog Niti On In The Conte X T Of Preg Nan C ...mentioning
confidence: 99%